Procurement of Food Ingredients in Food Production at Hotel Melia Makassar - Islami, Nur Annisa; Muhammad Salim, Muhammad Arfin; Jaya, Risman (Ann Publisher, 2026)
Aims. This research aims to understand how food ingredient procurement in Food Production at Hotel Melia Makassar operates and to identify the obstacles encountered. Methods. The research method is qualitative, with data collected through interviews and documentation. Result. The results of this research indicate that procurement of food ingredients is carried out through a systematic process, beginning with planning based on the Daily Market List (DML). This process, prepared by the kitchen team, involves the purchasing team's verification and supplier selection, the creation and delivery of Purchase Orders (PO), and the receiving team's receipt and inspection of materials in collaboration with the kitchen team. The food storage system strictly adheres to the First In, First Out (FIFO) principle, with clear storage zone divisions, including dry storage, chiller, and freezer, to ensure the quality and freshness of food ingredients. The main obstacles identified in this study include irregularities in the ordering process due to sudden order requests from the kitchen team, delivery delays from suppliers, discrepancies between the quality of received materials and established specifications, and challenges in managing food stock. Conclusion. Based on these findings, this research provides several strategic recommendations to improve food procurement efficiency in the hospitality industry, including enhancing interdepartmental coordination, implementing a more modern inventory system, conducting periodic evaluations of supplier performance, and developing staff capacity through structured training programs.